MENINGKATKAN HASIL BELAJAR IPAS KELAS IV MATERI MEMBANGUN MASYARAKAT YANG BERADAB MELALUI MODEL PROJECT BASED LEARNING (PJBL) BERBANTUAN MEDIA POP UP BLOCK DI SDN DALOPO 01 - Dhaniera Evin Sanjaya; Havif Wahyu Saputra; Wahyu Nur Hidayat; Melik Budiati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to improve social and natural science (IPAS) learning outcomes of fourth-grade students at SDN Dolopo 01 through the implementation of the Project-Based Learning (PjBL) model assisted by Pop Up Book media. This Classroom Action Research (CAR) utilized a descriptive qualitative approach conducted in two cycles, each consisting of planning, acting, observing, and reflecting phases. The subjects of this study were 13 fourth-grade students at SDN Dolopo 01, Madiun Regency. Data collection techniques included observation, questionnaires, and cognitive learning outcome tests. The results demonstrated a significant increase in student learning outcomes. In the pre-cycle phase, classical completeness was only 23.08% (3 students) with a class average of 62.31. Following the implementation in Cycle I, classical completeness rose to 61.53% (8 students) with an average score of 74.61. In Cycle II, after refining group organization into smaller teams and enhancing visual aids, classical completeness successfully reached 100% (13 students) with a class average of 92.30. Thus, the PjBL model assisted by Pop Up Book media is proven effective in improving students' IPAS learning outcomes, specifically on the topic of building a civilized society in elementary school.